Cyclization of ortho-hydroxycinnamates to coumarins under mild conditions: A nucleophilic organocatalysis approach - Boeck, Florian; Blazejak, Max; Anneser, Markus R.; Hintermann, Lukas (Beilstein Journal of Organic Chemistry, 2012)
(E)-Alkyl ortho-hydroxycinnamates cyclize to coumarins at elevated temperatures of 140–250 °C. We find that the use of tri-n-butylphosphane (20 mol %) as a nucleophilic organocatalyst in MeOH solution allows cyclization to take place under much milder conditions (60–70 °C). Several coumarins were prepared, starting from ortho-hydroxyarylaldehydes, by Wittig reaction with Ph3P=CHCO2Me to (E)-methyl ortho-hydroxycinnamates, followed by the phosphane catalyzed cyclization.
Keywords: catalysis; coumarins; heterocycles; mechanisms; organocatalysis; phosphanes